Analgesia Strategy on Cognitive Impairment after Spinal Anesthesia in Hip Surgery: A Meta-Analysis - Wardhana, Ardyan; Wika Pratama, Violetta; Yusuf, Muhammad; Faisal Aga, Mohammad (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Previous studies have indicated no significant difference in the incidence of cognitive impairment between general anesthesia and spinal anesthesia for hip surgery. However, the debate between general and spinal anesthesia merely scratches the surface. Within spinal anesthesia, components like pre- or post-surgery analgesia warrant consideration in optimizing strategies for geriatric patients. Objective: Hence, our study aims to analyze cognitive impairment incidence across various analgesia strategies as adjuncts to spinal anesthesia for hip surgery.Subject and Methods: We systematically conducted a search across two databases for randomized trials that investigated the incidence of cognitive impairment following hip surgery with spinal anesthesia. We analyzed pooled data for distinct pre or post-operative analgesia approaches. The primary outcome of this review was the occurrence of post-operative delirium (POD) within 7 days post-surgery and delayed neurocognitive recovery (DNCR), defined as cognitive impairment within the first 30 days after surgery.Results: A systematic search yielded 13 studies comparing analgesia modalities. Based on our meta-analysis results, we demonstrated that adequate analgesia administration could decrease the incidence of POD (RR: 0.37, 95% CI: 0.20 – 0.68; p < 0.05, moderate quality of evidence), DNCR at 24 hours post-operatively, 72 hours, and 4-7 days post-operatively.